FIRST CHECKLIST OF THE NON-ACARINE ARACHNIDS (CHELICERATA: ARACHNIDA) OF THE CHAPADA DIAMANTINA NATIONAL PARK, BRAZIL (Boletín de la Sociedad Zoológica del Uruguay, 2025)
This work aims to provide regionalized information on the non-acarine arachnids inhabiting the Brazilian Chapada Diamantina National Park (PARNA-CD), and its surroundings, to support studies for protecting endemic species and preventing human accidents by these animals. We used registers of five arachnological collections covering 36 years, validated by the world catalogs of each order. We found 67 arachnid species from five orders, 42 families, in the six municipalities surrounding PARNA-CD. Araneae (54 species) and Scorpiones (ten species) were the most representative orders. We found no records of the other orders except for Pseudoscorpiones (two species) and Amblypygi (one species). Only one spider species (Tmesiphantes hypogeus), and two scorpions (Troglorhopalurus lacrau and T. translucidus) were assessed on the IUCN criteria for conservation. Twenty-six species are endemic to Brazil, of which five have no records in any location other than PARNA-CD. At least one medically important species was encountered in each municipality, from the genera: Latrodectus, Loxosceles, Phoneutria, and Tityus. Given the recent rate of human-mediated changes (undue land-use) where several Brazilian caatinga areas were exposed, endemic species from this list should be the priority target for long-term ecological and behavioral studies.
Keywords: Arachnids; Biodiverstity; Caatinga; Bahia